2013
DOI: 10.1063/1.4807471
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of single biological cells and relation with cell viability

Abstract: This paper presents measurements of effective thermal conductivity of single biological cells (HeLa, NIH-3T3 J2, and hepatocyte). Such cellular-level measurements have not been performed previously, due to the small size (∼10 pl) of cells. The measurement uses the three-omega method with a nanoscale thermal sensor and a micro-well structure that confines the cell. The results provide a fundamental property to investigate the thermodynamics of cells. We also measured thermal conductivity of dead cells; results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The measured thermal conductivity of the different cell lines were slightly less than that of water (κ = 0.63 W mK −1 at 37 °C), which is consistent with the fact that water normally accounts for ≈80% of the cell's weight . Furthermore, the water content within living cells harbors a large composition of macromolecules, such as proteins, with calculated thermal conductivity less than water, thereby contributing to a lower thermal conductivity of living cells . We clearly observe that HeLa (cervical cancer) cells have different y ′ (and hence thermal properties) from the other breast cancer cell lines demonstrating that thermal properties are different among different types of cancer.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The measured thermal conductivity of the different cell lines were slightly less than that of water (κ = 0.63 W mK −1 at 37 °C), which is consistent with the fact that water normally accounts for ≈80% of the cell's weight . Furthermore, the water content within living cells harbors a large composition of macromolecules, such as proteins, with calculated thermal conductivity less than water, thereby contributing to a lower thermal conductivity of living cells . We clearly observe that HeLa (cervical cancer) cells have different y ′ (and hence thermal properties) from the other breast cancer cell lines demonstrating that thermal properties are different among different types of cancer.…”
Section: Resultssupporting
confidence: 75%
“…Since cellular response to overheating is diverse, ranging from improved diffusion rate across the cellular membrane to irreversible damage and protein denaturation, several techniques were developed to measure cellular thermal‐transport properties. 3‐Omega and thermal lensing techniques were employed to measure thermal conductivity and diffusivity (and effusivity as well), respectively. The cellular thermal diffusivity however is not studied as a thermal indicator of different types of cancers or different sub‐types of the same cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the heat transfer module in COMSOL, the above power dissipation is set as the thermal source, and the boundary of the region is set as a fixed temperature condition to simulate the normal tissue temperature. The thermal conductivity of the cell is set as approximately 0.6 W/m/K [Kyoo Park et al, 2013], and the initial and ambient temperature in and around the cell are set to 310.15 K (37°C), equal to the normal body temperature. The simulation results of the temperature rise in the single cell are shown in Figure 8.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al have shown that thermal conductivity of cells is very close to that of water, but may differ for various cell types. The measured thermal conductivities of HeLa, NIH-3T3 J2, and hepatocyte were , , and [ ] respectively 35 . A later study of Sotoma et al revealed much lower values of intracellular thermal conductivity using a heater-thermometer hybrid diamond nanosensor 36 .…”
Section: Resultsmentioning
confidence: 99%